"Wóz" albo "przewóz" – studium przypadku - Tyrpa, Anna (Słowiańska frazeologia gwarowa II, 2020)
WÓZ ALBO PRZEWÓZ – CASE STUDY The expression wóz albo przewóz, which is a call for making a decision (English counterpart: sink or swim), is well-known and frequently used, but its motivation has blurred. Dialectal records make it possible to reconstruct it. One of the meanings of the word przewóz is ‘a means of transport for crossing water, i.e. a boat or a ferry’. This meaning was maintained in folk dialects. Thus, wóz albo przewóz means an alternative – you can either choose wóz (cart) and travel on land, or przewóz (ferry/boat), and travel on water.